Effects of hyperbaric oxygen treatment and heparin on the survival of unipedicled venous flaps: An experimental study in rats - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2000)
The effects of hyperbaric oxygen (HBO) and heparin on the survival of the rat inferior epigastric venous flap were investigated. Preliminary transcutaneous oxygen measurements showed that partial oxygen pressure values of venous flaps increased at 2.5 ATA pressure while inhaling 100% oxygen. During the experiment, 128 venous flaps of two different sizes and 50 composite grafts were prepared bilaterally in 89 rats. Perivenous areolar tissue was removed from the pedicle vein in all flaps. Half of the venous flaps were isolated from the wound bed. Initial flap perfusion was tested by fluorescein injection during flap elevation. Four treatment groups were created: control, heparin, HBO, and HBO+heparin. After 6 days of treatment, the mean surviving flap area was calculated for each group, surviving flaps were reelevated, final flap perfusion was tested by fluorescein injection, and flaps were harvested for histological examination. The mean survival rates of the HBO (26.56%) and the HBO+heparin (36.87%) groups were significantly higher than the control (0%) and the heparin (0%) groups (p < 0.01). None of the composite grafts survived. Smaller flaps and nonisolated flaps survived better, although not significantly (p > 0.05). Veins were enlarged both clinically and histologically, Fluorescein uptake was delayed during initial flap elevation but was normal during reelevation. These findings imply that the rat inferior epigastric venous flap may be an ischemic flap with capillary circulation through a single venous pedicle, but it needs HBO treatment to survive, especially during the acute period. Heparin treatment, reducing the flap site, and presence of a vascular wound bed also improve survival rates.
Keywords: PERIVENOUS AREOLAR TISSUE; SKIN FLAPS; ISLAND FLAPS; ARTERIAL INFLOW; PLASMATIC IMBIBITION; DELAY PHENOMENON; LASER-DOPPLER; MICROCIRCULATION; REPERFUSION; FLOW